Gambaran Penderita Filariasis di Kabupaten Meranti Provinsi Riau Periode 2009-2014 - Esy Maryanti; Andriyani Andriyani; Suyanto Suyanto (Fakultas Kedokteran Universitas Riau, 2016)
Filariasis is one of the health problems in Indonesia due to its long-term effect on permanent disability ifnot treated properly. The purpose of this study is to describe people with filariasis in Meranti District ofRiau Province 2009-2014. The methods is a descriptive retrospective cross-sectional study using medicalrecords of patients diagnosed with filariasis in hospitals and all health centers in the District of Meranti.The result showed 38 patients with filariasis, and the highest case of filariasis were in Puskesmas PulauMerbau (94.8%). Distribution by gender, age and type of occupation as follows: men by 71%, 86.8% of thesubject belong to the age group 15-64 years old, and 65.8% were outdoor workers, 52.6% of lymphedemawas reported and the location of lymphedema mostly found on each leg (18.4%). All lymphedema werebelong to all the stage not exceed stage III. All cases of filariasis in this study were managed according tothe standard treatment.